Preliminary characterization of the acrasin of the cellular slime mold Polysphondylium violaceum. - Wurster, B (1976)
Some species of cellular slime mold do not respond to cyclic AMP as an acrasin, or chemoattractant. In one such species, Polysphondylium violaceum, we have isolated and purified its acrasin and determined some of its chemical properties, which lead us to believe it is a small molecule of less than 1500 daltons. One possibility is that it might be a peptide. The acrasin specifically attracts the amoebae of P. violaceum and P. pallidum and fails to do so for six species of Dictyostelium tested. We also have evidence for a specific acrasinase that inactivates the Polysphondylium acrasin.